Meningkatkan Kemampuan Komunikasi Horizontal Melalui Media Virtual Pasca Pandemi Covid-19 Guru SMP Bersinar Selambo, Provinsi Sumatera Utara - Ikwan Lubis; A.M Hatuaon Sihite; Maringan Sianturi; Nurin Natiqoh Lubis (Marsipature Hutanabe: Jurnal Pengabdian Kepada Masyarakat, 2024)
The Covid-19 pandemic has brought significant changes in various aspects of life, including in the way of communicating in an educational environment. Teachers at SMP Bersinar Selambo, North Sumatra Province, are faced with the challenge of maintaining effective horizontal communication amid the transition from face-to-face communication to virtual media. This community service program aims to improve horizontal communication skills between teachers through the use of virtual media after the Covid-19 pandemic. This activity was carried out by providing training and mentoring to teachers regarding the use of various virtual communication platforms, such as video conferencing applications and online collaboration tools. Through a participatory approach, the program also identifies the barriers teachers face in adapting to new technologies and offers solutions to improve their digital skills. The results of this program show a significant improvement in communication and collaboration skills between teachers, as well as a decrease in barriers to the use of communication technology. The conclusion of this community service activity is that improving digital skills and understanding of virtual media effectively supports better horizontal communication among SMP Bersinar Selambo teachers. This program is expected to be a model for other schools facing similar challenges, as well as contribute to creating an adaptive and collaborative educational environment in the digital era.